STRATEGI PENGEMBANGAN USAHA PETERNAKAN BABI DI KECAMATAN GETASAN KABUPATEN SEMARANG - Aprilianto Rinaldi, Evan Stefanus; Sunaryanto, Lasmono Tri; Nadapdap, Hendrik Johannes (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The consumption of pork in Java island approximately 194.O68 pigs in 2017, whereas the number of production of the pigs in this island only 133.794. This lackness of the supplement of 60.274 pigs shows the excessive amount of pork consumption in this island, therefore this will create a huge chance for pig breeders in Java island to develop their farms. This observation aimed to find out the strength, weakness, opportunity, and also thread factors related with the pig farming in Getasan district and to decide the appropriate strategy to be applied according to the analysis results. In this observation, the writer used the analysis of internal and external factors, SWOT analysis and QSPM to determine the strategy. As the result of the analysis there are 9 strategies, with the main strategy is increasing the production capacity in order to fulfill the market demanding with the total value 5.961.